(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
The text offers a preliminary overview of three instances of Mesopotamian sources from the magico-medical and literary sphere, in which the Seven demons (the Seven, Sebettu/Sibitti) are mentioned: some of the incantations for the exorcism of evil demons from the Udug-Hul incantations series; the Story of Gilgamesh and Huwawa (A and B); and Erra and Ishum (or the Poem of Erra/Erra). The text does not make an attempt to answer the question on whether these instances are really references to the same group of demonic Seven, for the Mesopotamian beliefs in demons span millennia, and different religious and cultural-political contexts, and there are various appearances of seven demons, but also of heroes and protectors. The ambivalence that appears in the conception of the Seven is shown through the different actions and roles of the demons in the incantations, as harbingers of disease and troubles; the seven heroes-protectors, sent by the deity in order to help Gilgamesh in his journey to the Cedar Forest (the Land of the living); and the seven servants, the weapons of Erra, who influence him to go on a raging chaotic campaign of violence and provoke the destruction of the world. Considering the decade’s long neglect in these areas, both of the beliefs in the evil incarnate, and the precious abundance of sources from the Mesopotamian culture, the goal of this text is to offer some introductory questions from these topics for the Macedonian public.